Effect Of Non-metal Elements (C, N, S) As Anionic Dopants On Electronic Structure Of Tio2-Anatase By Density-Functional Theory Approach - Hari Sutrisno (Molekul, 2016)
This article is a theoritical approach to calculate the electronic structure of undoped- and non-metal anions doped-TiO2-anatase. The objective of the research is to calculate abinitio the band structure and the density of states (DOS) of undoped-, C-, N-, and S-doped TiO2-anatase. Kohn-Sham equations are performed with the density functional theory (DFT) using the local density approximation (LDA) for exchange-correlation functional. The first-principle calculations were done using supercell (2x2x1) methods as implemented within Amsterdam Density Functional (ADF)-BAND version 2014.10. The ab-initio calculation of the band structures show that all samples are direct- and indirect-gap type semiconductor. The band gap of TiO2-anatase with DFT using LDA is 2.43 eV. The addition of C atom at 0.943% in 48 atoms produces width intermediate band about 0.76 eV, which is 0.38 eV above the valence band (VB) and 1.38 eV below the conduction band (CB). The addition of N atom at 1.103% and S atom at 2.478% in the lattice structure of TiO2-anatase resulted in the addition of the VB width to 0.47 eV and 0.11 eV, while the resulting gap between the VB and the CB to 1.97 eV and 2.33 eV, respectively.